Thromboangiitis Obliterans (Buerger's Disease)—Current Practices - Vijayakumar, Abhishek (Hindawi Publishing Corporation, 2013)
Thromboangiitis obliterans (TAO) is a nonatherosclerotic, segmental inflammatory disease that most commonly affects the small and medium-sized arteries and veins in the upper and lower extremities. Cigarette smoking has been implicated as the main etiology of the disease. In eastern parts of the world TAO forms 40–60% of peripheral vascular diseases. Clinical features and angiographic finding are the basis of early diagnosis of TAO. Abstinence from smoking is the only definitive treatment to prevent disease progression. Medical management in form of aspirin, pentoxyfylline, cilostazol, and verapamil increase pain-free walking distance in intermittent claudication, but long term usage fails to prevent disease progression in patients who continue to smoke. Surgical treatment in form of revascularization, lumbar sympathectomy, omentopexy, and Ilizarov techniques help reduce pain and promote healing of trophic changes. Newer treatment modalities like spinal cord stimulation, prostacyclin, bosentan, VEGF, and stem cell therapy have shown promising results. Latest treatment options include peripheral mononuclear stem cell, and adipose tissue derived mononuclear stem cells have been shown to be effective in preventing disease progression, decrease major amputation rates, and improving quality of life.